Strategizing Universal Design for Learning (UDL) Implementation: Enhancing Inclusive Education for Students with Disabilities in Higher Education - Sri Wahyuni; Yuni Pantiwati; Hari Sunaryo; Akhsanul In'am; Adolf Bastian (STAI Hubbulwathan Duri, 2025)
Inclusive higher education is essential for ensuring equitable access to learning, particularly for students with disabilities. Universal Design for Learning (UDL) provides a flexible instructional framework that accommodates diverse learning needs and promotes inclusion. This study employed a Systematic Literature Review (SLR) following the PRISMA model, using the Watase Uake application to identify and analyze scholarly works related to UDL implementation in Indonesian universities. Findings reveal that UDL positively impacts the academic experience of students with disabilities. Notable benefits include improved engagement and academic outcomes, with some cases reporting up to a 20% increase in student achievement. Effective strategies identified include flexible content delivery, adaptive assessment methods, and technology-enhanced instruction. However, several barriers persist, including limited faculty training, inadequate infrastructure, and high implementation costs. These were highlighted through qualitative insights and quantitative staff surveys. The results underscore the need for targeted interventions to overcome implementation challenges. The study proposes strategic measures such as comprehensive lecturer training, investment in multimodal learning tools, and more inclusive evaluation systems. This review offers practical recommendations to enhance UDL adoption in Indonesian higher education. By addressing current challenges, institutions can create a more inclusive academic environment that supports all learners, especially students with disabilities.